Preliminary study on the role of social presence in blended learning environment in higher education. - Jusoff, Kamaruzaman; Khodabandelou, Rouhollah (Canadian Center of Science and Education, 2009)
This paper contributes to the growing body of knowledge which identifies benefits for Blended Learning in the understanding of social processes role. It reports on an exploratory study into the role of social presence in blended learning environment. Employing a qualitative methodology, the study sought to understand social presence of learners in Blended Learning environment. The paper presents the definition of social presence as described by blended learning instructors and it’s role in the development of Blended Learning environment.